Fractionation and immunoreactivity of Mycobacterium bovis AN5 sonicated antigens - GUPTA, V K; RAM, G C (The Indian Journal of Animal Sciences, 2014)
Mycobacterium bovis AN5 sonic extraetwas fractionated using get permeation and anion exchange chromatography. The immunoreactivity of fractionated antigens was evaluated using M. bovis AN5 serum in ELISA. Out of several fractionated regions obtained from the sonic extract, the more immunogenic regions were heterogenous polypetides of 68 and 71kDa and 79 and 81 leDa and homogenous polypeptides of 56 and 48kDa molecular masses. These 4 fractionated antigens showed a greater reactive response to anti M. bollis serum in ELISA. Imrnunoblotting on one diamensional SDS PAGE separated sonic extract revealed 8 seroreactive bands of 81, 71, 65, 56,28,22,18 and 14kDa. Most of the fractionated antigens showed cross reactivity with other Mycobacterium spp. in ELISA except 56kDa antigens which showed less cross reactivity in ELISA. It is concluded that these antigens might be possessing imrnunodominant epnopes for the humoral and cellular responses.